The Rulings on Capital Return Guarantees in Mudhârabah (Profit Sharing) Contracts: A Comparative Study Between The AAOIFI Sharia Standards and The DSN-MUI Fatwas - Agus Putra, Panji Adam; Saripudin, Udin; Nurrachmi, Intan (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2023)
Abstract. This study aims to identify and analyze the legal constructions of capital guarantees in the AAOIFI Sharia Standards and the DSN-MUI Fatwas. This is normative legal research with a specific comparative approach. This research shows that the rulings of the AAOIFI Sharia Standards are more reassuring and prioritize the principle of ihtiyāth (precaution). Meanwhile, the legal provision of the DSN-MUI fatwas, allowing the capital manager to guarantee a return on business capital, is a commitment in the form of tabarru from the fund manager. T he commitment should be fulfilled since it is a wa’ad mulzim (binding promise). T his legal provision of the DSN-MUI Fatwas is a form of innovative ijtihad that seems different from the opinions of most scholars used as the legal basis of the AAOIFI. However, the DSN-MUI’s fatwa is supported by various arguments and is more applicative. Abstrak. Penelitian ini bertujuan untuk mengetahui dan menganalisis konstruksi hukum jaminan modal dalam Standar Syariah AAOIFI dan Fatwa DSN MUI. Penelitian ini merupakan penelitian hukum normatif dengan pendekatan komparatif. Penelitian ini menunjukkan bahwa ketentuan Standar Syariah AAOIFI lebih tepat dan mengedepankan prinsip ihtiyāth (kehati-hatian). Sedangkan ketentuan hukum fatwa DSN-MUI yang memperbolehkan pengelola modal dengan jaminan pengembalian modal adalah komitmen dalam bentuk tabarru dalam pengelolaan dana. Komitmen tersebut harus dipenuhi karena merupakan wa’ad mulzim (janji mengikat). Ketentuan hukum Fatwa DSN MUI ini merupakan bentuk ijtihad inovatif yang nampaknya berbeda dengan pendapat kebanyakan ulama yang dijadikan landasan hukum AAOIFI. Namun, fatwa DSN-MUI didukung oleh berbagai argumentasi dan lebih aplikatif.